2008
DOI: 10.1007/s10404-008-0282-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a surface-tension gradient on the performance of a micro-grooved heat pipe: an analytical study

Abstract: We investigate effects of surface-tension gradients on the performance of a micro-grooved heat pipe in this work. The surface-tension gradient force is accounted for in the present model, and expressions for radius of curvature, liquid pressure, liquid velocity, and maximum heat throughput are found analytically using a regular perturbation technique. With a favorable surface-tension gradient, the liquid pressure drop across the heat pipe can be decreased by *90%, and the maximum heat throughput can be increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 32 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…J.Ha et al [42] and V. Sartre et al [43] also studied aluminum/ammonia triangle MHP. Balram Suman et al [44] studied the effect of surface tension gradient on the performance of microgrooved heat pipes, finding that the effect of surface tension gradient increased with the increase of the corner angle of the polygonal heat pipe. The change of liquid temperature and surfactant concentration have an undesirable effect on the surface tension gradient.…”
Section: 24mentioning
confidence: 99%
“…J.Ha et al [42] and V. Sartre et al [43] also studied aluminum/ammonia triangle MHP. Balram Suman et al [44] studied the effect of surface tension gradient on the performance of microgrooved heat pipes, finding that the effect of surface tension gradient increased with the increase of the corner angle of the polygonal heat pipe. The change of liquid temperature and surfactant concentration have an undesirable effect on the surface tension gradient.…”
Section: 24mentioning
confidence: 99%
“…Suman and his colleagues conducted studies of micro heat pipes with various crosssectional geometries using 1D transport model. Besides the capillary pressure and the wall shear stress [61], they have incorporated the effect of body force (gravity) [62][63][64], the inertia in the liquid [62,63], heat conduction through the substrate [65], and the linear variation of the surface tension [63] (e.g., due to an interfacial temperature gradient). However, their treatment of transport in the gas phase was incomplete in all of these studies.…”
Section: One-sided Transport Modelsmentioning
confidence: 99%
“…The results revealed that the surface with a gradient wettability increased the maximum heat input of the MHP up to 49.7%, compared with that of uniform surface wettability. The effect of surface-tension gradient on the thermal performance of a MHP has been numerically investigated by Suman [57]. Results show that the liquid pressure drop across the MHP can be decreased by about 90%, and the maximum heat throughput can be increased by about 20% with a favorable surface-tension gradient.…”
Section: Novel Designs For Performance Improvementmentioning
confidence: 99%